1993
DOI: 10.1021/ic00056a018
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, solution structure, and reactivity of oxygen-bound amides on cobalt(III)

Abstract: A series of pentaamminecobalt(II1) amide complexes containing oxygen-bonded amides are reported. The electronic structure of the amide ligand remains delocalized on coordination to the metal ion, and there is evidence for increased polarization of the amide upon coordination. There is restricted rotation about the carbon-nitrogen bond as shown by separate NMR signals for the amide nitrogen substituents. Also the unsymmetrically substituted formamides (HCONHCH3 and HCONHC~HS) are in both the 2 and E configurati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
23
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 2 publications
2
23
0
Order By: Relevance
“…The formate ion in I resulted from the hydrolysis of N , N ′‐diethylformamide employed as the solvent in the synthesis. Similar hydrolysis of N , N ′‐dimethylformamide molecules forming formic acid has been reported earlier . The Mn−O bond lengths are in the range of 2.075(3)–2.306(3) Å, (average=2.188 Å) and the O‐Mn‐O bond angles are in the range 71.90(10) to 175.56(11)° (Table S1 in the Supporting Information).…”
Section: Resultssupporting
confidence: 79%
“…The formate ion in I resulted from the hydrolysis of N , N ′‐diethylformamide employed as the solvent in the synthesis. Similar hydrolysis of N , N ′‐dimethylformamide molecules forming formic acid has been reported earlier . The Mn−O bond lengths are in the range of 2.075(3)–2.306(3) Å, (average=2.188 Å) and the O‐Mn‐O bond angles are in the range 71.90(10) to 175.56(11)° (Table S1 in the Supporting Information).…”
Section: Resultssupporting
confidence: 79%
“…For background to the use of DMF, see: Kolthoff et al (1970); Pastoriza-Santos & Liz-Marzan (1999); Kimmerle & Eben (1975); Gescher (1993); Zhou et al (1996); Matwiyoff (1966). For amide complexes, see: Rao et al (1984); Angus et al (1993); Khum & Maclntyre (1965).…”
Section: Related Literaturementioning
confidence: 99%
“…Due to the model properties for peptides, the amide complexes is of continuing interest. Crystallographic studies have shown that in complexes, the amides are bonded to the metal atom by using their carbonyl oxygen (Rao et al, 1984;Angus et al, 1993;Khum & Maclntyre, 1965).…”
Section: Data Collectionmentioning
confidence: 99%
“…10,13 In the case of formanilides, the preference for the Z-isomer was less pronounced. 9,12 In contrast to the hydantoins 11, the methylene protons of the achiral malonic acid diamides 12f-j are not diastereotopic, and their signals appear as quartets. A single-crystal X-ray analysis was carried out on the 2formamidomalonic acid diamide 12f, as an example, confirming its structure and the Z-configuration ( Figure 1).…”
mentioning
confidence: 99%
“…This clearly indicates that the N-substituted formamides 12 are present as Z-isomers, because for E-iso-mers much larger coupling constants ( 3 J > 10 Hz) have been detected. [9][10][11][12] The E/Z ratio, as determined on the basis of 1 H NMR assignments, was reported for several Nmonoalkylated formamides, including those with tert-alkyl groups. The proportion of the Z-isomer was generally higher (≥70%).…”
mentioning
confidence: 99%